2013
DOI: 10.4314/jab.v65i0.89576
|View full text |Cite
|
Sign up to set email alerts
|

Root-yield performance of pre-release sweet potato genotypes in Kenya

Abstract: Objective: The focus of this study was to evaluate the yield and stability of superior sweet potato cultivars for release in Kenya. This is the first attempt to document experimental results that have led to the first and so far only sweet potato variety release in Kenya. Methodology: Ten national performance trials laid out as randomized complete block designs were performed on 14 sweet potato (Ipomoea batatas (L.) Lam.) genotypes in two geographical locations of Kenya. The trials were conducted to select loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
5
6
0
Order By: Relevance
“…The significant interactions effect may imply that genotype interact differently with seasons and environment which caused variations in the TTRY across environments over time. This is in agreement with similar studies (Adebola et al, 2013;Mcharo et al, 2013), who found variations in root yield stability of sweetpotato cultivars across environments. The model partitioned the interactions into three significant Interaction Principle Component Analysis axes (IPCA) in the order of their relevance that is IPCA1 explained 75.76%, IPCA2 18.86% and IPCA3 5.38% of the variance.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The significant interactions effect may imply that genotype interact differently with seasons and environment which caused variations in the TTRY across environments over time. This is in agreement with similar studies (Adebola et al, 2013;Mcharo et al, 2013), who found variations in root yield stability of sweetpotato cultivars across environments. The model partitioned the interactions into three significant Interaction Principle Component Analysis axes (IPCA) in the order of their relevance that is IPCA1 explained 75.76%, IPCA2 18.86% and IPCA3 5.38% of the variance.…”
Section: Resultssupporting
confidence: 93%
“…This may signify how change in seasons affected genotypes' TTRY performance and stability in multi-environments over time. This finding corresponded to similar studies done by Mcharo et al (2013). Vitae (16.40 t/ha) and Kabode (16.85 t/ha) persistently maintained low yield in all the environments in the three years (Table 1), however, their average yield recorded in this study is still within the Variety release check yield range (16.0 t/ha to 34 t/ha) reported (Kapinga et al, 2010;Mwanga et al, 2009).…”
Section: Resultssupporting
confidence: 93%
“…These traits formed mega-environments and, consequently, require fewer environment sites to make recommendations. The significant environment effects on root yield are consistent with previous studies (Tumwegamire et al 2016, Mcharo andNdolo 2013). As expected, cultivar Ndou performed well under farmer conditions over several sites; thus, it findings need to be further validated using multi-location and multi-season data to confirm repeatability and for future recommendation of the cultivars.…”
Section: Discussionsupporting
confidence: 89%
“…To produce suitable genotypes for multiple environments, G´Es should be accounted for and assessed in plant breeding programs (El Soda et al, 2014). Previous studies indicated significant G´Es in yield and yield components and in quality traits of sweetpotato (Grüneberg et al, 2005;Caliskan et al, 2007;Osiru et al, 2009;Mcharo and Ndolo, 2013). Previous studies indicated significant G´Es in yield and yield components and in quality traits of sweetpotato (Grüneberg et al, 2005;Caliskan et al, 2007;Osiru et al, 2009;Mcharo and Ndolo, 2013).…”
Section: Multienvironment Performance Of Newmentioning
confidence: 99%
“…Relative to other major staple crops, such as maize (Zea mays L.) and wheat (Triticum aestivum L.), little information is available on G´Es in sweetpotato (Grüneberg et al, 2005). Previous studies indicated significant G´Es in yield and yield components and in quality traits of sweetpotato (Grüneberg et al, 2005;Caliskan et al, 2007;Osiru et al, 2009;Mcharo and Ndolo, 2013).…”
mentioning
confidence: 99%